2008
DOI: 10.1002/dvdy.21450
|View full text |Cite
|
Sign up to set email alerts
|

Trichostatin A (TSA) improves the development of rabbit‐rabbit intraspecies cloned embryos, but not rabbit‐human interspecies cloned embryos

Abstract: The interspecies somatic cell nuclear transfer (iSCNT) technique for therapeutic cloning gives great promise for treatment of many human diseases. However, the incomplete nuclear reprogramming and the low blastocyst rate of iSCNT are still big problems. Herein, we observed the effect of TSA on the development of rabbit-rabbit intraspecies and rabbit-human interspecies cloned embryos. After treatment with TSA for 6 hr during activation, we found that the blastocyst rate of rabbit-rabbit cloned embryos was more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
3
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 49 publications
3
59
3
2
Order By: Relevance
“…Together, with hypermethylation of porcine fibroblast nuclei , this may be the reason for failure of nucleoli formation in porcine-rabbit iSCNT embryos. However, rabbit oocytes were shown to support preimplantation development of embryos derived from nuclei of several species, including bovine , Capra ibex (Jiang et al 2005), chicken , camel and Tibetan antelope (Zhao et al 2006), macaca (Yang et al 2003), cat and panda (Wen et al 2005), and even human (Shi et al 2008). However, microarray analysis failed to detect significant human genome reprogramming in human-rabbit iSCNT embryos (Chung et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Together, with hypermethylation of porcine fibroblast nuclei , this may be the reason for failure of nucleoli formation in porcine-rabbit iSCNT embryos. However, rabbit oocytes were shown to support preimplantation development of embryos derived from nuclei of several species, including bovine , Capra ibex (Jiang et al 2005), chicken , camel and Tibetan antelope (Zhao et al 2006), macaca (Yang et al 2003), cat and panda (Wen et al 2005), and even human (Shi et al 2008). However, microarray analysis failed to detect significant human genome reprogramming in human-rabbit iSCNT embryos (Chung et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, supplementation of reprogramming factors and even substitution of individual factors with small molecules has been demonstrated to drastically increase the efficiency of reprogramming. Components used include HDAC inhibitors such as valproic acid, suberoylanilide hydroxamic acid and trichostatin A, DNA methyltransferase inhibitors such as 5'-azacytidine (5'-azaC) and RG108, histone methyltransferase inhibitors such as BIX01294 and Ca-channel activators such as R(+)Bay K 8644 (Huangfu et al, 2008a;Shi et al, 2008). Addition of valproic acid, which is also beneficial in SCNT (Huangfu et al, 2008a), increased reprogramming efficiency 100-fold and allowed for successful reprogramming to occur without the addition of factors Klf4 and c-myc, two known oncogenes (Huangfu et al, 2008b).…”
Section: Methods For Generation Of Induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…On the other hand, many studies have reported production of iSCNT morulae and blastocysts (BL) also when nucleus donor cells and recipient oocytes had a very distant taxonomical relation, like in the case of inter-family bovine-pig (Dominko et al 1999, Uhm et al 2007, inter-order cat-and panda-rabbit (Wen et al 2005), camel-and Tibetan antelope-rabbit (Zhao et al 2006), human-rabbit (Shi et al 2008), dog-pig (Sugimura et al 2009), tiger-pig (Hashem et al 2007, human-bovine (Chang et al 2003, Illmensee et al 2006, Li et al 2008 or inter-classes chicken-rabbit combinations. However, this approach remains ineffective.…”
Section: Introductionmentioning
confidence: 99%